HUBUNGAN INTENSITAS PENGGUNAAN GAME ONLINE KEKERASAN DENGAN PEILAKU AGRESI PADA PELAJAR DI WONOSOBO - Rizki Eko Prasetio; Hartosujono Hartosujono (Universitas Sarjanawiyata Tamansiswa, 2013)
AbstractÂ This study was conducted to determine the correlation between the intensity of use of online games with violent content and aggressive behavior in students in Wonosobo. Subjects were 100 secondary school students in Wonosobo. The sampling technique in this study using purposive sampling. This research method using quantitative methods. Data collection instrument using the scale of aggression and intensity scale online games use violence content. Analysis of the data by using the technique of Pearson product moment correlation using SPSS program for Windows 17. The results showed no relationship between the intensity of use of online games berkonten violent and aggressive behavior in students in Wonosobo. The correlation coefficient (r xy) -0.184, p = 0.067, rules that are used in testing the hypothesis is p <0.05, so the hypothesis is not accepted.Keywods : intensity of use of online games with violent content, aggression behavior